已知[√(a-3)]+b=2,(√a^2+4a+4)+(√b^2-4b+4
2个回答
[√(a-3)]+b=2
√(a-3)>=0,0
相关问题
已知4A2+B2+4A=2B-2,求[(3A-B)(3A+B)-A(A-4B)+B2]÷(-4A) 已知X²-
已知√a-3+b=2,化简(√a^2+4a+4)+(√b^2-4b+4
呃 是已知已知√(a-3)+b=2,化简(√a^2+4a+4)+(√b^2-4b+4
已知a-2b-1/2,ab=2,求-a^4b^2+4a^3b^3-4a^2b^4的值
已知A=2a+3,B=-4a²+3a-1,C=3a²-4a+4,求4A+{2B-(3B-2C)+6B
已知a≠b,求证a^4+6a^2 b^2+b^4>4ab(a^2+b^2)
已知:a-b=0,求a^3-(2a^4b^3-a^2b)-ab^2-b^3+2a^3^b^4
a、b是实数,如果已知4/a4-4/a2-3=0,且b4+2b2-3=0,那么a4xb4+4/a4=
已知:|a-b+1|+√2a-3b-4=0,求4a+b∧2
已知2a+b=(-4,3),a-2b=(3,4),求a+b的绝对值